Preparation method and application of cobalt Prussian blue analogue / carbon nanotube composite material

By using the cobalt Prussian blue object/carbon nanotimal composite material as a lithium sulfur battery orthoplastor material, it uses its strong polysulfide adsorption capacity and high electricality to solve the low -sulfide shuttle effect and low conductivity in lithium sulfur batteries The problem realizes the efficient electrochemical performance improvement and simplification process.

CN113782728BActive Publication Date: 2025-01-28ZHEJIANG WANGDIAN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111082118.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-15
Publication Date
2025-01-28
Estimated Expiration
2041-09-15

AI Technical Summary

Technical Problem

Lithium sulfur batteries lead to low Coulomb efficiency and rapid capacity attenuation due to low conductivity and volume changes of sulfur and discharge products, resulting in destruction of the positive electrode structure, and the shuttle effect of soluble polysulfides.

Method used

Using cobalt Prussian blue objects/carbon nanotubes (PBA/CNT) composite materials as a lithium sulfur battery positive electrode material, combined by one step, use PBA's functional groups and central ion activity sites to strongly adsorb, and use CNT to pass CNT through CNT The high -conductivity and comparison area increase the sulfur content and electrochemical properties.

Benefits of technology

The high -ratio capacity, excellent electrochemical cycle performance and magnification performance were achieved, effectively improved the electrochemical properties of lithium sulfur batteries, simplified the preparation process and reduced costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113782728B_ABST
    Figure CN113782728B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a cobalt Prussian blue analogue / carbon nanotube composite material, belonging to the technical field of lithium batteries. The preparation method comprises: adding a metal salt and an organic ligand to deionized water in proportion, stirring at room temperature with a magnetic stirrer to obtain a pink turbid liquid, centrifuging, washing and drying after standing for 24 hours to obtain a pink solid powder. The pink solid powder, tris(hydroxymethyl)aminomethane and dopamine hydrochloride are placed in a mixed solvent of deionized water and ethanol in proportion, stirring at room temperature to obtain a black turbid liquid, centrifuging, washing and drying after standing for 24 hours to obtain a black solid powder. The black solid powder is calcined in one step to obtain the composite material. The material can be used as a positive electrode material in lithium-sulfur batteries. The present invention has the advantages of simple process and easy scalability. The prepared material can effectively adsorb polysulfides and inhibit the shuttle effect. It is used as a carrier in lithium-sulfur batteries and has excellent electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries and relates to a preparation method and application of a lithium-sulfur battery positive electrode composite material. Background Art

[0002] Lithium-sulfur (Li-S) batteries are secondary batteries with sulfur as the positive electrode and lithium as the negative electrode. They have a high theoretical specific capacity (1675 mAh g -1 ) and energy density (2600Wh kg -1 ), which is 3-5 times that of current commercial lithium-ion batteries. At the same time, elemental sulfur has natural advantages such as low cost, environmental friendliness and abundant reserves. Therefore, Li-S batteries are considered to be the next generation of energy storage systems with great potential. However, there are still many urgent problems that need to be solved in lithium-sulfur batteries: 1) The low conductivity of sulfur and discharge products leads to slow redox reaction kinetics and low sulfur utilization; 2) The volume change of discharge products leads to the destruction of the positive electrode structure; 3) The shuttle effect of soluble polysulfides between the two electrodes leads to low coulombic efficiency and rapid capacity decay. Therefore, the application of sulfur positive electrodes has encountered great challenges.

[0003] At present, in order to solve the above problems, researchers usually adopt the method of improving the support material to improve the electrochemical performance of lithium-sulfur batteries. For example, metal organic framework (MOF) has been widely studied because of its adjustable pore structure, inherent functional groups and central ions, which can well limit the shuttling effect of polysulfides. Making full use of the central ion active sites in MOF materials that have a strong adsorption effect on polysulfides is an effective way to alleviate the excessive dissolution of polysulfides. For example, Ni 2 + 、Co 2+ Ni-CoPBA. However, the poor conductivity of these materials leads to slower redox reaction kinetics between polysulfides and MOFs, low sulfur utilization and poor rate performance. In order to improve the conductivity of the carrier material, MOF materials coated with graphene and penetrated by carbon nanotubes are prepared, such as hollow MOF penetrated by carbon nanotubes, MOF-derived nitrogen-doped porous carbon anchored on graphene and other composite materials. These materials have an efficient conductive network, which can increase the sulfur content and electrolytic penetration, and show excellent electrochemical properties. However, the cumbersome preparation process limits its further application. For example, in the synthesis process, the carrier material needs to be prepared first and then acid-etched to form a hollow structure, and then the carrier / carbon nanotube composite material is synthesized by electrostatic action. Summary of the invention

[0004] The first object of the present invention is to provide a method for preparing a cobalt Prussian blue analogue / carbon nanotube (PBA / CNT) composite material, wherein the lithium-sulfur battery positive electrode material prepared by the method has a strong chemical adsorption capacity and fast redox reaction kinetics for polysulfides, and exhibits high specific capacity, excellent electrochemical cycle performance and rate performance.

[0005] The first object of the present invention is achieved through the following technical solutions.

[0006] The preparation method of the cobalt Prussian blue analogue / carbon nanotube composite material of the present invention comprises the following steps.

[0007] (1) Metal cobalt salt and trisodium citrate were placed in deionized water at a mass ratio of 1:2-3 to form a uniform solution, which was dispersed in a 0.023 mmol / mL potassium cobalt cyanide solution and stirred with a magnetic stirrer at room temperature to obtain a pink turbid solution. After standing for 24 h, the solution was centrifuged, washed, and dried to obtain a pink solid powder.

[0008] (2) The pink solid powder and dopamine hydrochloride were dispersed in a tris(hydroxymethyl)aminomethane buffer solution at a mass ratio of 1:1-3, and stirred at room temperature to obtain a black turbid liquid. After standing for 24 h, the solution was centrifuged, washed, and dried to obtain a black solid powder.

[0009] The tris(hydroxymethyl)aminomethane) buffer solution is prepared by dissolving tris(hydroxymethyl)aminomethane in a mixed solvent of ethanol and deionized water at a ratio of 10 mmol / L, wherein the mass ratio of ethanol to deionized water is 1:1.

[0010] (3) The black solid powder was placed in a tubular furnace, heated from room temperature to 600°C-700°C in an inert gas atmosphere for 2-4 h, and then naturally cooled to room temperature to obtain a PBA / CNT composite material.

[0011] (4) The PBA / CNT composite material and sublimated sulfur are uniformly mixed in a mass ratio of 1:3-10. The obtained black solid powder is heated from room temperature to 150-180°C under an inert gas atmosphere, kept at the constant temperature for 12-24 h, and then naturally cooled to room temperature to obtain a sulfur-loaded PBA / CNT (PBA / CNT / S) lithium-sulfur battery positive electrode material.

[0012] Preferably, in step (1), the metal cobalt salt is one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate and cobalt acetate tetrahydrate.

[0013] Preferably, in step (1), the mass ratio of the metal cobalt salt to trisodium citrate is 1:2.

[0014] Preferably, in step (2), the mass ratio of the pink solid powder to dopamine hydrochloride is 1:1, and the volume ratio of deionized water to ethanol is 1:1.

[0015] Preferably, in step (3), the heating rate is 2-4°C / min, and the inert gas is one of argon and nitrogen.

[0016] Preferably, in step (4), the mass ratio of the PBA / CNT composite material to the sublimated sulfur is 1:3.

[0017] The second object of the present invention is to use the above-mentioned cobalt Prussian blue analogue / carbon nanotube composite material as a positive electrode material in a lithium-sulfur battery.

[0018] The present invention synthesizes a PBA / CNT composite material by one-step calcination. The inherent functional groups and central ions of PBA have strong adsorption capacity for polysulfides and can well limit the shuttle effect of polysulfides. At the same time, PBA has excellent specific surface area and hierarchical pore structure, making it an excellent sulfur carrier. The PBA-coated CNT can increase the sulfur content and effectively adsorb polysulfides due to its high specific strength, large specific surface and high conductivity, inhibit the shuttle effect of polysulfides, and enhance the electrochemical performance of lithium-sulfur batteries. Therefore, the preparation of low-cost, high-performance PBA / CNT sulfur composite positive electrode materials has a very far-reaching significance and broad prospects in the field of lithium-sulfur batteries.

[0019] Compared with the prior art, the present invention has the following beneficial effects.

[0020] (1) The preparation steps and equipment are simple, the cost is low, and it is easy to prepare on a large scale industrially.

[0021] (2) PBA / CNT composites as S carriers can effectively improve the electrochemical performance of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The diagram of the experimental device for preparing PBA / CNT composite materials is shown in FIG. 1 , wherein 1 is an argon gas bottle, 2 is a quartz tube, 3 is a heating furnace, and 4 is a ceramic boat.

[0023] Figure 2 The diagram of the experimental device for preparing the PBA / CNT / S composite material is shown in FIG. 1 , wherein 1 is an argon gas bottle, 2 is a quartz tube, 3 is a heating furnace, 4 is a ceramic boat, and 5 is a glass dish. DETAILED DESCRIPTION

[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] The methods described in the following examples are conventional methods unless otherwise specified, and the materials and reagents are commercially available unless otherwise specified.

[0026] Example 1.

[0027] Take 0.776 g of potassium cobalt cyanide and dissolve it in deionized water at 0.023 mmol / mL. Then take 0.76 g of cobalt nitrate hexahydrate and 1.52 g of trisodium citrate and dissolve them in deionized water and slowly add them to the above potassium cobalt cyanide solution. Stir with a magnetic stirrer at room temperature for 3 h to obtain a pink turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a pink solid powder. Take 100 mg of pink solid powder and 100 mg of dopamine hydrochloride and disperse them in 10 mmol / L tris(hydroxymethyl)aminomethane buffer solution. Stir at room temperature for 12 h to obtain a black turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a black solid powder. Place the black solid powder in a tubular furnace and use an experimental device such as Figure 1 As shown, the temperature was raised from room temperature to 700 °C in an argon gas atmosphere at a heating rate of 2 °C / min and kept constant for 3 h. The mixture was cooled to room temperature and taken out to obtain a PBA / CNT composite material.

[0028] The PBA / CNT composite material and sublimed sulfur were mixed evenly in a mass ratio of 1:3 and spread on the bottom of a flat-bottomed glass tube with a diameter of 10 mm and a height of 10 mm, and placed in a tube furnace. The experimental apparatus was used as Figure 2 As shown, the temperature was raised from room temperature to 155 °C in an argon atmosphere, kept constant for 12 h, cooled to room temperature, and taken out to obtain a PBA / CNT sulfur composite material. The PBA / CNT sulfur composite material, acetylene black, and PVDF were coated on carbon paper at a ratio of 8:1:1, and assembled into a lithium-sulfur battery with a separator, a lithium sheet, and an electrolyte. The charge and discharge test was carried out at a rate of 0.2 C, and the results are shown in Table 1.

[0029] Example 2.

[0030] Take 0.776 g of potassium cobalt cyanide and dissolve it in deionized water at 0.023 mmol / mL. Then take 0.76 g of cobalt chloride hexahydrate and 2.28 g of trisodium citrate and dissolve them in deionized water and slowly add them to the above potassium cobalt cyanide solution. Stir with a magnetic stirrer at room temperature for 3 h to obtain a pink turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a pink solid powder. Take 100 mg of pink solid powder and 200 mg of dopamine hydrochloride and disperse them in 10 mmol / L tris(hydroxymethyl)aminomethane buffer solution. Stir at room temperature for 12 h to obtain a black turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a black solid powder. Place the black solid powder in a tubular furnace and use an experimental device such as Figure 1As shown, in an argon gas atmosphere, the temperature was raised from room temperature to 700 °C at a heating rate of 2 °C / min, maintained at a constant temperature for 2 h, cooled to room temperature, and taken out to obtain a PBA / CNT composite material.

[0031] The PBA / CNT composite material and sublimed sulfur were mixed evenly in a mass ratio of 1:6 and spread on the bottom of a flat-bottomed glass tube with a diameter of 10 mm and a height of 10 mm, and placed in a tube furnace. The experimental apparatus was used as Figure 2 As shown, the temperature was raised from room temperature to 150 °C in an argon atmosphere, kept constant for 24 h, cooled to room temperature, and taken out to obtain a PBA / CNT sulfur composite material. The PBA / CNT sulfur composite material, acetylene black, and PVDF were coated on carbon paper at a ratio of 8:1:1, and assembled into a lithium-sulfur battery with a separator, a lithium sheet, and an electrolyte. The charge and discharge test was carried out at a rate of 0.2 C, and the results are shown in Table 1.

[0032] Example 3.

[0033] Take 0.776 g of potassium cobalt cyanide and dissolve it in deionized water at 0.023 mmol / mL. Then take 0.76 g of cobalt acetate tetrahydrate and 2.28 g of trisodium citrate and dissolve them in deionized water and slowly add them to the above potassium cobalt cyanide solution. Stir with a magnetic stirrer at room temperature for 3 h to obtain a pink turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a pink solid powder. Take 100 mg of pink solid powder and 300 mg of dopamine hydrochloride and disperse them in 10 mmol / L tris(hydroxymethyl)aminomethane buffer solution. Stir at room temperature for 12 h to obtain a black turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a black solid powder. Place the black solid powder in a tubular furnace and use an experimental device such as Figure 1 As shown, in an argon gas atmosphere, the temperature was raised from room temperature to 700 °C at a heating rate of 2 °C / min, maintained at a constant temperature for 4 h, cooled to room temperature, and taken out to obtain a PBA / CNT composite material.

[0034] The PBA / CNT composite material and sublimed sulfur were mixed evenly in a mass ratio of 1:10 and spread on the bottom of a flat-bottomed glass tube with a diameter of 10 mm and a height of 10 mm, and placed in a tube furnace. The experimental apparatus was used as Figure 2 As shown, the temperature was raised from room temperature to 180 °C in an argon atmosphere, kept constant for 12 h, cooled to room temperature, and taken out to obtain a PBA / CNT sulfur composite material. The PBA / CNT sulfur composite material, acetylene black, and PVDF were coated on carbon paper at a ratio of 8:1:1, and assembled into a lithium-sulfur battery with a separator, a lithium sheet, and an electrolyte. The charge and discharge test was carried out at a rate of 0.2 C, and the results are shown in Table 1.

[0035] Example 4.

[0036] Take 0.776 g of potassium cobalt cyanide and dissolve it in deionized water at 0.023 mmol / mL. Then take 0.76 g of cobalt nitrate hexahydrate and 1.52 g of trisodium citrate and dissolve them in deionized water and slowly add them to the above potassium cobalt cyanide solution. Stir with a magnetic stirrer at room temperature for 3 h to obtain a pink turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a pink solid powder. Take 100 mg of pink solid powder and 100 mg of dopamine hydrochloride and disperse them in 10 mmol / L tris(hydroxymethyl)aminomethane buffer solution. Stir at room temperature for 12 h to obtain a black turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a black solid powder. Place the black solid powder in a tubular furnace and use an experimental device such as Figure 1 As shown, in an argon gas atmosphere, the temperature was raised from room temperature to 600 °C at a heating rate of 2 °C / min, maintained at a constant temperature for 3 h, cooled to room temperature, and taken out to obtain a PBA material.

[0037] PBA material and sublimed sulfur were mixed evenly in a mass ratio of 1:3 and spread on the bottom of a flat-bottomed glass tube with a diameter of 10 mm and a height of 10 mm. The tube furnace was placed and the experimental device was used as follows. Figure 2 As shown, the temperature was raised from room temperature to 155 °C in an argon atmosphere, kept constant for 12 h, cooled to room temperature, and taken out to obtain a PBA sulfur composite material. The PBA sulfur composite material, acetylene black, and PVDF were coated on carbon paper at a ratio of 8:1:1, and assembled into a lithium-sulfur battery with a separator, a lithium sheet, and an electrolyte. The charge and discharge test was carried out at a rate of 0.2 C, and the results are shown in Table 1.

[0038] Example 5.

[0039] Take 0.776 g of potassium cobalt cyanide and dissolve it in deionized water at 0.023 mmol / mL. Then take 0.76 g of cobalt chloride hexahydrate and 2.28 g of trisodium citrate and dissolve them in deionized water and slowly add them to the above potassium cobalt cyanide solution. Stir with a magnetic stirrer at room temperature for 3 h to obtain a pink turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a pink solid powder. Take 100 mg of pink solid powder and 200 mg of dopamine hydrochloride and disperse them in 10 mmol / L tris(hydroxymethyl)aminomethane buffer solution. Stir at room temperature for 12 h to obtain a black turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a black solid powder. Place the black solid powder in a tubular furnace and use an experimental device such as Figure 1 As shown, in an argon gas atmosphere, the temperature was raised from room temperature to 600 °C at a heating rate of 2 °C / min, maintained at a constant temperature for 2 h, cooled to room temperature, and taken out to obtain a PBA material.

[0040] The PBA composite material and sublimed sulfur were mixed evenly in a mass ratio of 1:6 and spread on the bottom of a flat-bottomed glass tube with a diameter of 10 mm and a height of 10 mm, and placed in a tube furnace. Figure 2 As shown, the temperature was raised from room temperature to 150°C in an argon atmosphere, kept constant for 24 h, cooled to room temperature, and taken out to obtain a PBA sulfur composite material. The PBA / sulfur composite material, acetylene black, and PVDF were coated on carbon paper at a ratio of 8:1:1, and assembled into a lithium-sulfur battery with a separator, a lithium sheet, and an electrolyte. The charge and discharge test was carried out at a rate of 0.2 C, and the results are shown in Table 1.

[0041] Example 6.

[0042] Take 0.776 g of potassium cobalt cyanide and dissolve it in deionized water at 0.023 mmol / mL. Then take 0.76 g of cobalt acetate tetrahydrate and 2.28 g of trisodium citrate and dissolve them in deionized water and slowly add them to the above potassium cobalt cyanide solution. Stir with a magnetic stirrer at room temperature for 3 h to obtain a pink turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a pink solid powder. Take 100 mg of pink solid powder and 300 mg of dopamine hydrochloride and disperse them in 10 mmol / L tris(hydroxymethyl)aminomethane buffer solution. Stir at room temperature for 12 h to obtain a black turbid liquid. After standing for 24 h, centrifuge, wash and dry to obtain a black solid powder. Place the black solid powder in a tubular furnace and use an experimental device such as Figure 1 As shown, in an argon gas atmosphere, the temperature was raised from room temperature to 600 °C at a heating rate of 2 °C / min, maintained at a constant temperature for 4 h, cooled to room temperature, and taken out to obtain a PBA material.

[0043] The PBA composite material and sublimed sulfur were mixed evenly in a mass ratio of 1:10 and spread on the bottom of a flat-bottomed glass tube with a diameter of 10 mm and a height of 10 mm, and placed in a tube furnace. Figure 2 As shown, the temperature was raised from room temperature to 180 °C in an argon atmosphere, kept constant for 12 h, cooled to room temperature, and taken out to obtain a PBA sulfur composite material. The PBA sulfur composite material, acetylene black, and PVDF were coated on carbon paper at a ratio of 8:1:1, and assembled into a lithium-sulfur battery with a separator, a lithium sheet, and an electrolyte. The charge and discharge test was carried out at a rate of 0.2 C, and the results are shown in Table 1.

[0044] Table 1. Charge and discharge test results of lithium-sulfur batteries prepared with pole pieces obtained in different embodiments

[0045]

Claims

1. A method for preparing a cobalt Prussian blue analogue / carbon nanotube composite material, characterized in that The following steps are involved: (1) A metal cobalt salt and trisodium citrate were placed in deionized water at a mass ratio of 1:2-3 to form a uniform solution, which was dispersed in a 0.023 mmol / mL potassium cobalt cyanide solution. The solution was stirred at room temperature with a magnetic stirrer to obtain a pink turbid solution. After standing for 24 h, the solution was centrifuged, washed, and dried to obtain a pink solid powder. (2) The pink solid powder and dopamine hydrochloride are dispersed in a tris(hydroxymethyl)aminomethane buffer solution at a mass ratio of 1:1-3, stirred at room temperature to obtain a black turbid liquid, and after standing for 24 hours, centrifuged, washed, and dried to obtain a black solid powder; The tris(hydroxymethyl)aminomethane) buffer solution is prepared by dissolving tris(hydroxymethyl)aminomethane in a mixed solvent of ethanol and deionized water at a ratio of 10 mmol / L, wherein the mass ratio of ethanol to deionized water is 1:1; (3) placing the black solid powder in a tube furnace, heating it from room temperature to 600°C-700°C in an inert gas atmosphere for 2-4 h, and then naturally cooling it to room temperature to obtain a PBA / CNT composite material; (4) The PBA / CNT composite material and sublimated sulfur are uniformly mixed in a mass ratio of 1:3-10. The obtained black solid powder is heated from room temperature to 150-180°C under an inert gas atmosphere, kept at the constant temperature for 12-24 h, and then naturally cooled to room temperature to obtain a sulfur-loaded PBA / CNT (PBA / CNT / S) lithium-sulfur battery positive electrode material.

2. The method for preparing a cobalt Prussian blue analogue / carbon nanotube composite material according to claim 1, characterized in that In step (1), the metal cobalt salt is one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, and cobalt acetate tetrahydrate.

3. The method for preparing a cobalt Prussian blue analogue / carbon nanotube composite material according to claim 1, characterized in that In step (1), the mass ratio of the metal cobalt salt to trisodium citrate is 1:

2.

4. The method for preparing a cobalt Prussian blue analogue / carbon nanotube composite material according to claim 1, characterized in that In step (2), the mass ratio of the pink solid powder to dopamine hydrochloride is 1:

1.

5. The method for preparing a cobalt Prussian blue analogue / carbon nanotube composite material according to claim 1, characterized in that In step (3), the heating rate is 2-4°C / min, and the inert gas atmosphere is one of argon and nitrogen.

6. The method for preparing a cobalt Prussian blue analogue / carbon nanotube composite material according to claim 1, characterized in that In step (4), the mass ratio of the PBA / CNT composite material to the sublimated sulfur is 1:

3.

7. Use of the cobalt Prussian blue analogue / carbon nanotube composite material prepared by the method for preparing the cobalt Prussian blue analogue / carbon nanotube composite material according to any one of claims 1 to 6 as a positive electrode material in a lithium-sulfur battery.

Citation Information

Patent Citations

  • Porous nitrogen-doped carbon supported cobalt nano-material, preparation method and application thereof

    CN108736028A

  • Preparation method and application of composite material with elemental cobalt coated with carbon nanotubes

    CN110571439A